2014
DOI: 10.1037/a0036126
|View full text |Cite
|
Sign up to set email alerts
|

Art schema effects on affective experience: The case of disgusting images.

Abstract: Can we experience depictions of repulsive objects more positively when we watch them as part of a work of art? We addressed this question by using a scenario approach in a laboratory setting designed to activate two different cognitive schemata: participants viewed the same pictures framed either as art photographs or as documentary photographs for educational purposes. Self-reports of the positivity, the negativity, and the intensity of the affective responses yielded three results. First, participants experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 46 publications
7
76
2
Order By: Relevance
“…Aiming to clarify this interplay, Wagner, Menninghaus, Hanich, and Jacobsen () examined the impact of verbally elicited cognitive schemas about art on the affective processing of images. Participants viewed the same stimuli, which depicted disgusting objects, framed as either artistic photographs or as educational documentary materials.…”
Section: Contributions Of Leder Et Al's () Model Of Aesthetic Experimentioning
confidence: 99%
“…Aiming to clarify this interplay, Wagner, Menninghaus, Hanich, and Jacobsen () examined the impact of verbally elicited cognitive schemas about art on the affective processing of images. Participants viewed the same stimuli, which depicted disgusting objects, framed as either artistic photographs or as educational documentary materials.…”
Section: Contributions Of Leder Et Al's () Model Of Aesthetic Experimentioning
confidence: 99%
“…A study that presented photographs of disgusting matter as either art photography or documentary photographs made for purposes of hygiene instruction found higher levels of positive affect in the art-framing group (Wagner et al 2014); at the same time, reported feelings of disgust did not differ between the two conditions. Accordingly, a study on perceived sadness and anxiety in a fictionversus-nonfiction framing did not find any differences for the two conditions (Goldstein 2009).…”
Section: Empirical Evidencementioning
confidence: 92%
“…The DEM predicts that these schemata, activated by art framing, should influence the experience of negative emotions. However, Wagner et al (2014) and Gerger et al (2014) cited as supporting studiesfound no such influence. The DEM is grounded not on empirical data but on assumptions about art and emotion derived from philosophical and poetic theorizing.…”
Section: The Enjoyment Of Negative Emotions In the Experience Of Magicmentioning
confidence: 92%
See 2 more Smart Citations